Using Item Option Characteristics Curve (IOCC) to Unfold Misconception on Chemical Reaction - Qudratuddarsi, Hilman; Ramadhana, Nurhikma; Indriyanti, Nor; Indayanti Ismail, Ayu (Journal of Tropical Chemistry Research and Education, 2024)
Misconceptions can significantly hinder the learning process. To address this, various diagnostic instruments such as two-tier (2TMC), three-tier, and four-tier multiple-choice questions have been introduced. However, as the number of tiers increases, identifying misconceptions becomes more complex. Therefore, this study employs the Item Option Characteristics Curve (IOCC) to identify misconceptions by calculating the probability of each option being selected. The Representational Systems and Chemical Reactions Diagnostic Instrument (RSCRDI) was administered to 185 pre-service teachers across three universities in Indonesia. The data was analyzed using Winstep software to generate the IOCC for each item. The analysis revealed that each item in the phenomenon and reasoning tiers contains distractors that could interfere with the option selected by pre-service chemistry teachers. While the alternative answers identified using traditional methods (commonly used since the introduction of 2TMC) were mostly similar to those identified by IOCC, the IOCC provided more detailed insights. Specifically, it highlighted unexpected curves after 0 logits, identified less effective distractors, and revealed inconsistencies in the most influential distractors. These findings suggest that the IOCC provides richer, more detailed information and can be a valuable alternative framework for analyzing 2TMC items to unfold misconceptions.